Prognostic Factors and Clinical Features of Neonatal Splenic Rupture/Hemorrhage: Two Cases Reports and Literature Review - Chang, Han-Pi; Fu, Ren-Huei; Lin, Jainn-Jim; Chiang, Ming-Chou (Frontiers in Pediatrics, 2021)
Background Neonatal splenic rupture/hemorrhage (SRH), an extremely rare and potentially fatal presentation, can spontaneously resolve without surgical treatment; However, treatment approaches remain controversial. The present study aimed to describe and analyze the clinical features and therapies of neonatal SRH and therapeutic approaches. Methods We present the cases of two patients and review another 37 cases reported in English-literature. The literature search included all articles published in PUBMED from inception between January 1968 and December 2019. Demographic data, precipitating factors, clinical characteristics including presenting symptoms and signs, presenting time, age at SRH presentation, imaging findings, as well as treatments and outcomes were analyzed. Results In addition to the two cases treated at our hospital, 37 neonates with SRH were reported during the study period. The rate of full-term neonates was 72% (28/39). The cause was idiopathic in most cases, and congenital coagulation disorders were underlying causes in 13% (5/39) of the cases. The most common presenting symptom and sign of neonatal SRH were pallor or anemia, followed by abdominal discoloration/distension. Additionally, 18% (7/39) of the cases presented with scrotal hematoma or swelling. The age at SRH presentation ranged between 3 hours and 5 days of age. Abdominal ultrasonography or computed tomography was used as the diagnostic tool. Twenty-seven cases (69%) received surgical management. The prognosis was comparable between the neonates treated with splenectomy and those treated with nonsurgical approaches. The mortality rate was 18% (7/39) in the study cohort. SRH presentation at ≤12 hours of age was associated with higher mortality compared to SRH presenting time at >12 hours of age (odds ratio 25.0, 95% CI 2.514-248.575, p=0.001). Conclusion Our literature review revealed that the mortality rate of neonatal SRH was 18% and that the mortality risk was higher in neonates presenting with SRH symptoms and signs at ≤12 hours of age.